2021
DOI: 10.1002/ijc.33451
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation age as a biomarker for cancer

Abstract: Cancer is well established as an age‐associated disease, and there is substantial overlap in the molecular, cellular and physiological changes observed with both ageing and the progression of cancer. Age‐specific declines in resilience mechanisms such as DNA repair or epigenetic maintenance may contribute to the development of cancer. These declines may be assessed through biomarkers that measure biological age and through the related concept of “age acceleration”. Epigenetic clocks, assessed through DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…At the same time, HorvathAA is a stable indicator of metabolic aging processes [52]. However, we have found that HorvathAA and HannumAA indicators are highly correlated, as reported by Lau et al [53], in contrast with others who reported low correlation values [54]. Our results confirmed that the GrimAge clock is higher in smokers (past and current) and in relation to alcohol intake, as also found by Kresovich et al [54]; in fact, the clock is constructed as the composite of 8 DNA methylation-based markers for plasma proteins and selfreported smoking packs [32] making it more responsive to smokers.…”
Section: Sensitivity Analysis: Sex-stratifiedsupporting
confidence: 72%
“…At the same time, HorvathAA is a stable indicator of metabolic aging processes [52]. However, we have found that HorvathAA and HannumAA indicators are highly correlated, as reported by Lau et al [53], in contrast with others who reported low correlation values [54]. Our results confirmed that the GrimAge clock is higher in smokers (past and current) and in relation to alcohol intake, as also found by Kresovich et al [54]; in fact, the clock is constructed as the composite of 8 DNA methylation-based markers for plasma proteins and selfreported smoking packs [32] making it more responsive to smokers.…”
Section: Sensitivity Analysis: Sex-stratifiedsupporting
confidence: 72%
“…A number of strategies have been utilized for predicting an aging process but often face the issue of low accuracy in prediction, which obstructs the potentials of several developments in such a domain. Nowadays, DNA methylation (DNAm) data have been emerging as a popular research area employed to predict the epigenetic age of organisms [ 5 , 6 ]. Recently, it has been shown that the process of aging is extremely associated with the alterations of DNAm in genome-particular situations.…”
Section: Introductionmentioning
confidence: 99%
“…Because genome-wide DNA methylation studies show shared epigenomic features between aging and cancer, providing explanations for their possible molecular links [ 12 , 13 , 14 ], the role for DNAm age in carcinogenesis has been recently explored. The obtained results indeed indicate that DNAmaa increases cancer risk, promote cancer initiation or progression, and predict poor patient outcomes in different types of cancer [ 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, in some other cancers, DNAmad is associated with aggressive diseases and shorter survival.…”
Section: Introductionmentioning
confidence: 70%